Current physiological parameters of horse riders in equine specific education - Jones, C.; Boden, E. (Journal of Human Sport & Exercise, 2017)
In equestrian activities, the majority of riders will prioritise their horse`s performance and fitness over their own, as they are under the impression that the horse is the only athlete in the partnership. Previous studies have discovered that amateur riders are physically weaker and have a poorer aerobic ability compared to that of other sports (Halliday, et al, 2011), and that an increased aerobic capacity helps to determine a rider`s performance in competition (Devienne and Guezennec, 2000), therefore additional physical activity, and general fitness is essential. The aim of this study is to determine the current physiological parameters of female horse riders that are studying equine specific higher education courses. In this longitudinal experimental study, female higher education students (n=18), categorised by their year groups (year one, year two and year three), and staff (n=6) participated in a maximal exertion programme to reach fatigue to allow for various physiological measurements adapted from Boden and Randle (2015) to be taken during the course of this physical activity. During the data collection period, each participant was required to wear a heart rate (HR) monitor and express their feelings regarding tiredness on a fatigue visual numeric scale. The multiple measurements taken include; basal fitness using a 20m shuttle run (bleep test), sit and reach test and resting HR, blood lactate concentrations, body weight, body fat (four skin fold calliper method), height, reaction times and grip strength. Followed by a maximal graded exercise test on a treadmill with increasing speed and incline to induce fatigue, allowing for HR and velocity at which maximal oxygen uptake occurs (VO2max) to be measured with a Douglas Bag. The results of the grouped data will be statistically analysed by using a two way analysis of variance (ANOVA) and furthermore, a one way ANOVA will be used to assess the fitness parameters of individuals in relation to the number of hours riding per week. Pursuing the pilot study for this study it is evident that not all participants pushed themselves to maximum and that horse riders do not have a sufficient standard of physical fitness or a high level of physiological attributes to send achieve a greater amount in their sport.